Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Answer:
3840
Step-by-step explanation:
Given expression:
4(x+5)(x+1)(x+3)(x - 3)
To:
Evaluate the expression ; for x = 5.
Solution:
- 4(x+5)(x+1)(x+3)(x - 3)
Evaluate x = 5 :
- 4(5+5)(5+1)(5+3)(5 - 3)
Simplify using PEMDAS rule:
P : Parentheses
E : Exponents
M : Multiplication
D : Division
A : Addition
S : Subtraction
- (4)(10)(5+1)(5+3)(5−3)
- 40(5+1)(5+3)(5−3)
- (40)(6)(5+3)(5−3)
- (240(5+3)(5−3)
- (240)(8)(5−3)
- 1920(5−3)
- (1920)(2)
- 3840
Hence, after evaluating the given expression for x = 5 , the answer'll be 3840.
Hi student, let me help you out! :)
. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .
We are asked to evaluate
[tex]\large\pmb{4(x+5)(x+1)(x+3)(x-3)}[/tex] for x=5.
[tex]\triangle~\fbox{\bf{KEY:}}[/tex]
- Use PEMDAS. With the help of this acronym, we will not make any mistakes in the Order of Operations!
Here's what PEMDAS stands for:
P=Parentheses
E=Exponents
M=Multiplication
D=Division
A=Addition
S=Subtraction
So, let's start computing...
///\\\///\\\///\\\///\\\///\\\////\\\///\\\///\\\///\\\///\\//\\\///\\\///\\\///\\\\///\\\\///\\\///\\\///\
Evaluating the expression
First, substitute 5 for x:
[tex]\star~\large\pmb{4(5+5)(5+1)(5+3)(5-3)}[/tex]
Now, use the Order of Operations.
The first operation here is:
[tex]\dag[/tex] P=Parentheses
So we need to perform the operations inside the parentheses first:
[tex]\star~\large\pmb{4(10)(6)(8)(2)}[/tex]
The next operation is multiplication, since we don't have any exponents here:
[tex]\star~\large\pmb{40\times6\times8\times2}[/tex]
Multiply!
[tex]\star~\Large\pmb{3840}~~\square\!\!\!\!\!\checkmark[/tex]
That's the value of the expression 4(x+5)(x+1)(x+3)(x-3) for x=5.
Hope it helps you out! :D
Ask in comments if any queries arise.
#StudyWithBrainly
~Just a smiley person helping fellow students :)
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.